Трансформація християнських уявлень у традиційній календарній обрядовості (історико-етнографічне дослідження на матеріалах Волинського Полісся) - Ковальчук Н., Н. (Народна творчість та етнографія, 2007)
The article touches upon the problem of the syncretism of pagan and Christian ritual symbols in the folk calendar. The interaction of the two outlooks in Ukrainian spiritual culture is analyzed. The main aspects in the transformational processes in the structure of calendar systems are emphasized. The retrospective view on the following problem is showed.